Multinationals, innovation, and institutional context: IPR protection and distance effects - Bruno, Randolph Luca; Crescenzi, Riccardo; Estrin, Saul; Petralia, Sergio (Journal of International Business Studies, 2022)
Abstract We characterize the knowledge production process whereby the inventive capabilities of the firm generate innovation output in highly inventive multinational enterprises (MNEs). We explore the sensitivity of this relationship to the strength of intellectual property rights (IPR) protection across the MNEs R&D subsidiaries. We argue that MNE innovative performance will be enhanced when the firm’s R&D activities are based in locations where IPR protection is stronger. Moreover, when considering the internal geography of the MNEs R&D activities, innovation performance depends on the distance between the home- and host-country IPR regime. Thus, innovation performance is worse, as the difference between home and host IPR regimes increases. Finally, we explore asymmetries in this relationship, in particular that the deterioration is more marked when MNEs locate their R&D activities in host economies with IPR protection significantly less strict than in their home country. We test these ideas using a unique new dataset about the most innovative MNEs in the world, an unbalanced panel of around 900 MNEs observed for the period 2004 to 2013 and find strong support for all our hypotheses.